Cholecystectomy for Acute Cholecystitis After Renal Transplantation - Varga, M; Kudla, M; Vargova, L; Fronek, J (Transplantation proceedings, 2016)
BACKGROUND: The aim of our study was to evaluate the rate of surgical complications, patient outcomes, and impact on graft function in renal transplant recipients in whom cholecystectomy for acute cholecystitis was performed. METHODS: We reviewed data on transplant patients from January 1, 2006, to December 31, 2013. The subgroup of patients who required subsequent cholecystectomy for acute cholecystitis was assessed, and their data were further analyzed. RESULTS: Thirty-one patients who underwent cholecystectomy for acute cholecystitis after renal transplantation were included in the study. Clinical signs such as pain in the right upper quadrant, temperature >38°C, and elevation in bilirubin levels occurred in 20 (64.5%), 8 (25.8%), and 3 (9.7%) patients, respectively. Ultrasound signs of acute cholecystitis were present in 27 patients (87.1%). In terms of laboratory values, white blood cell counts >10 × 10(9)/L occurred in 17 patients (54.8%), and C-reactive protein levels >40 mg/L were reported in 21 patients (67.7%). The conversion rate to open surgery was 32.3% (10 patients). In 13 cases, acalculous cholecystitis was present (41.9%). The average serum creatinine level 1 year after cholecystectomy had no statistically significant differences. One patient required temporary dialysis during the postoperative period (with subsequent graft recovery), and 1 graft was lost. CONCLUSIONS: Acute cholecystitis in kidney transplant recipients is a serious complication, with frequent difficulties related to evaluation and diagnosis. Because clinical signs could be very mild compared with severity of gallbladder affliction, there is little room if any for conservative treatment in these patients. We have not noticed adverse impact of acute cholecystitis on 1-year graft function.
Keywords: cholecystektomie laparoskopická; senioři; Leukocyte Count; C-Reactive Protein; přežívání štěpu; akutní cholecystitida; Retrospective Studies; transplantace ledvin; C-reaktivní protein; Middle Aged; Renal Dialysis; mužské pohlaví; Graft Survival; Adult; mladý dospělý; Postoperative Complications; Conversion to Open Surgery; Young Adult; ultrasonografie; ženské pohlaví; Kidney Transplantation; retrospektivní studie; Humans; Cholecystitis, Acute; lidé středního věku; konverze na otevřenou operaci; Ultrasonography; počet leukocytů; dialýza ledvin; Cholecystectomy, Laparoscopic; dospělí; Female; Aged; pooperační komplikace; lidé; Male